Predictive Role of ADA in Bronchoalveolar Lavage Fluid in Making the Diagnosis of Pulmonary Tuberculosis - Fariba Binesh; Abolhassan Halvani (Pulmonary Medicine)
Current diagnostic tests for tuberculosis (TB) are time-consuming. The aim of this study was to evaluate the diagnostic usefulness of ADA in bronchoalveolar lavage fluid in patients with pulmonary TB. A cross-sectional study was performed in Yazd, Iran, between 2009 and 2010. Patients suspected of pulmonary TB with negative sputum smear for AFB were included in the study. Mean ADA levels in BAL fluids were measured and compared between study groups. Sixty-three patients were enrolled in the study among which 15 cases had pulmonary TB, 33 had pulmonary diseases other than TB, and 15 subjects with normal bronchoscopy results were considered as controls. Mean ADA levels in BAL fluid were 4.13±2.55, 2.42±1.06, and 1.93±0.88, respectively. This rate was significantly higher in the pulmonary TB group compared to the other two groups (P=0.001). Using ROC curve with a cut-off value of 3.5 IU/L, the highest sensitivity (57%) and specificity (84%) were obtained in diagnosis of TB. The results showed that although ADA activity in BAL fluid of pulmonary TB patients was higher than those seen in other diseases, a negative test does not rule out pulmonary TB.